If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 2) + -1(y + 6) = 0 Reorder the terms: (2 + 2y) + -1(y + 6) = 0 Remove parenthesis around (2 + 2y) 2 + 2y + -1(y + 6) = 0 Reorder the terms: 2 + 2y + -1(6 + y) = 0 2 + 2y + (6 * -1 + y * -1) = 0 2 + 2y + (-6 + -1y) = 0 Reorder the terms: 2 + -6 + 2y + -1y = 0 Combine like terms: 2 + -6 = -4 -4 + 2y + -1y = 0 Combine like terms: 2y + -1y = 1y -4 + 1y = 0 Solving -4 + 1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 1y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 1y = 0 + 4 1y = 0 + 4 Combine like terms: 0 + 4 = 4 1y = 4 Divide each side by '1'. y = 4 Simplifying y = 4
| 0=16t^2-300t+1000 | | 8(e-5)=2(3e-8) | | -1.5(-4.7)-4.7= | | 19-3n=-29 | | 14-x=-10 | | 3a+8=y | | -4j-2(3j+5)=-6j+2(j+2) | | 104=8(v+6) | | 4-3=2+8 | | 7x-750=5x-600 | | 3x-6(5+x)=-4(x+7) | | 6-6=9x+5x | | 2d+18=12-6(d+7) | | -1.5(-1.5)-4.7= | | -(-x)x=96 | | 10x=4x-28 | | 4.1(1-5.8v)=3.5v-14.996 | | -a+2b-8a= | | [2/3x-2/3]=2/3 | | 4j-2(3j+5)=-6j+2(j+2) | | -1.5x-1.5-4.7= | | 17y-13y=20 | | -3(x+2)+2(x+1)=2x+11 | | 100[0.09(q+4)]= | | 4a-3b=49 | | .25t=-3 | | 3-2=2+2 | | 35x+9=-10 | | -(-6+k)=27-4k | | 2v^2-31v+18=8v^2-2+2v | | -10=x-3-1 | | 14r-7(r+7r)+11r=15 |